2002
DOI: 10.1590/s0101-81752002000500019
|View full text |Cite
|
Sign up to set email alerts
|

Eunice rubra Grube (Annelida, Polychaeta, Eunicidae), a redescription based on the holotype and Brazilian specimens

Abstract: ABSTRACT. Based on features of the holotype and seven Brazilian specimens examined under stereomicroscope,light microscope, and scanning electron microscope, Eunice rubra Grube, 1856 is redescribed, allowing for intraspecific variation and providing information on characters not included in a previous redescription. Characters important for the taxonomy of the genus varied widely, a1though in some cases because of fixation artefacts. KEY WORDS. Eunice rubra, Eunicidae, Polychaeta, taxonomy, south-eastern Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In a recent study, Nogueira (2000) analysed the polychaetes living in colonies of 0 KLVSLGD in the same area as the present work and reported that these animals, especially members of the families Syllidae, Spionidae, Serpulidae, and Eunicidae, in this order, were very abundant. As a result of that study, several new taxa (genera and species) are currently being described (Nogueira andAmaral, 2000, 2001;Nogueira and ten Hove, 2000;Nogueira and Rizzo, 2001;Nogueira et al, 2001 a and b;Nogueira and KnightJones, 2002;Nogueira and San Martín, 2002;Steiner et al, 2002). According to Fauchald and Jumars (1979), the feeding guilds of the most representative families of polychaetes in the present study observed suggested that they were very important on these communities, controlling populations of microcrustaceans, feeding on suspended materials, and on detritus and bacteria entrapped in coral mucus.…”
Section: Wdwlvwlfdo Dqdo\vlvmentioning
confidence: 98%
“…In a recent study, Nogueira (2000) analysed the polychaetes living in colonies of 0 KLVSLGD in the same area as the present work and reported that these animals, especially members of the families Syllidae, Spionidae, Serpulidae, and Eunicidae, in this order, were very abundant. As a result of that study, several new taxa (genera and species) are currently being described (Nogueira andAmaral, 2000, 2001;Nogueira and ten Hove, 2000;Nogueira and Rizzo, 2001;Nogueira et al, 2001 a and b;Nogueira and KnightJones, 2002;Nogueira and San Martín, 2002;Steiner et al, 2002). According to Fauchald and Jumars (1979), the feeding guilds of the most representative families of polychaetes in the present study observed suggested that they were very important on these communities, controlling populations of microcrustaceans, feeding on suspended materials, and on detritus and bacteria entrapped in coral mucus.…”
Section: Wdwlvwlfdo Dqdo\vlvmentioning
confidence: 98%
“…However, diagnostic features of many Leodice species have been well studied under the names of Eunice species by the previous works (Hartman 1944, Day 1967, Miura 1977, 1986, Fauchald 1992, Carrera-Parra and Salazar-Vallejo 1998, Zanol et al 2000, Steiner et al 2002, Zanol et al 2007, Wu et al 2013b). The new species of the present study can be discriminated from its relatives by the distinguishing morphological features provided by these previous works.…”
Section: Systematic Accountsmentioning
confidence: 99%
“…Among them, L. rubra is especially similar to L. duplexa sp. n. in the presence of paired subacicular hooks in some chaetigers (Fauchald 1992, Steiner et al 2002). However, these two species differ from each other by the number of branchial filaments and aciculae: L. duplexa sp.…”
Section: Systematic Accountsmentioning
confidence: 99%
See 2 more Smart Citations